(untitled) (Journal of the College of Basic Education, 2025)
The research aims to (reveal the relationship between self-confidence and aesthetic preference among students of the Department of Art Education, and the research focused in the first chapter of it on the problem of research and its importance and limits and the definition of some of its terms. The second chapter dealt with the concept of self-confidence and its relationship to some factors in the personality, and aesthetic preference and its role in art and art education and concluded the chapter with some indicators and previous studies, and the third chapter included the methodology consisting of a community and a sample of third grade students Department of Art Education - College of Fine Arts - University of Baghdad and the researcher built two tests for the variables of the research and used statistical means to verify the test, As for the fourth chapter, the researcher has reached the most important results: 1 - There is a correlation between self-confidence and aesthetic preference produced by the results of the statistical analysis adopted by the researcher. The most important conclusions were: 1- Attention to the subject of taste and art criticism, which is one of the axes of contemporary art education as it contributes to the development of the student’s ability to choose and prefer his things, whether in the educational or social situation. Finally, the researcher recommended 1- Attention to theoretical subjects such as aesthetic and taste education, art criticism and artistic psychology as they open scientific horizons for. students to experiment with preparing research in this field